Natural history in early modern France : the poetics of an epistemic genre - Garrod, Raphaële; Smith, P. J. (Paul J.) (Intersections: Interdisciplinary studies in early modern culture, 2018)
Natural History in Early Modern France offers a longue durée account of recurring poetic structures of the genre through case studies spanning from the Renaissance to the eve of the nineteenth century. These case studies reveal the lasting epistemic importance of bookish knowledge and commonplacing in the natural-historical description from Belon to Buffon. They also highlight the French reception of Baconianism. Natural History in Early Modern France makes a case for the literary status of the genre by attending to the permanence of its 'Plinian' features, such as wonders. Natural history was not only concerned with increasingly rational modes of ordering natural particulars: this book reveals its enduring social, affective, spiritual, and aesthetic underpinnings. Contributors are: Peter Anstey, Susan Broomhall, Isabelle Charmantier, Arlette Fruet, Raphaële Garrod, Paul Gibbard, Dana Jalobeanu, Myriam Marrache-Gouraud, Stéphane Schmitt, Paul J. Smith, and Stéphane Van Damme.